2021
DOI: 10.1016/j.neuroimage.2021.118071
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of Alzheimer's disease using creatine chemical exchange saturation transfer magnetic resonance imaging

Abstract: Detecting Alzheimer’s disease (AD) at an early stage brings a lot of benefits including disease management and actions to slow the progression of the disease. Here, we demonstrate that reduced creatine chemical exchange saturation transfer (CrCEST) contrast has the potential to serve as a new biomarker for early detection of AD. The results on wild type (WT) mice and two age-matched AD models, namely tauopathy (Tau) and A β amyloidosis (APP), indicated that CrCEST contrasts of the cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 86 publications
5
45
0
Order By: Relevance
“…Igarashi et al demonstrated a reduced level of glutamate measured by using glutamate CEST, as an indicator of synaptic dysfunction, in the parietal cortex but not in the hippocampus of 5 × FAD mice compared to wild-type mice [ 129 ]. Using creatine CEST MRI, Chen et al demonstrated a reduced level of creatine in the cortex and corpus callosum of APP/PS1 mice compared to wild-type mice at 6 months-of-age [ 145 ]. Chen et al showed a reduced saturation transfer difference for the composite protein amide proton in APP/PS1 mice compared to the age-matched wild-type mice [ 144 ].…”
Section: Neurochemical Changes Detectionmentioning
confidence: 99%
“…Igarashi et al demonstrated a reduced level of glutamate measured by using glutamate CEST, as an indicator of synaptic dysfunction, in the parietal cortex but not in the hippocampus of 5 × FAD mice compared to wild-type mice [ 129 ]. Using creatine CEST MRI, Chen et al demonstrated a reduced level of creatine in the cortex and corpus callosum of APP/PS1 mice compared to wild-type mice at 6 months-of-age [ 145 ]. Chen et al showed a reduced saturation transfer difference for the composite protein amide proton in APP/PS1 mice compared to the age-matched wild-type mice [ 144 ].…”
Section: Neurochemical Changes Detectionmentioning
confidence: 99%
“…However, it may serve as a tool for investigating cerebral pH changes in AD. Chen et al have investigated CrCEST in mouse models of AD: Aβ-related (APP/PS1 mice) and tau-related (Tau4RΔK mice) [ 146 ]. As a simple asymmetry analysis can confound results due to signals present on the opposite side of the spectrum, the authors use a different approach to analysis by converting their acquired z-spectrum into an R-spectrum: rotating-frame relaxation spectrum [ 147 ] to obtain the rotating frame relaxation rate (R Cr ).…”
Section: Chemical Exchange Saturation Transfer (Cest)mentioning
confidence: 99%
“…The authors conclude that the R Cr change in both AD models is due to a decrease in pH. Chen et al further demonstrate that a reduction in mouse brain pH caused by hypercapnia results in a decrease in both CrCEST and APT, and use phantom studies to determine that both the CrCEST signal intensity and exchange rate, R Cr at 2 ppm are linearly dependent on pH over a physiological range [ 146 ]. The region of R Cr decrease observed in the APP/PS1 model corresponds to the areas where reactive forms of both astrocytes and microglia are present as confirmed by GFAP and IBA1 (Ionized calcium-Binding Adapter molecule 1) immunostaining.…”
Section: Chemical Exchange Saturation Transfer (Cest)mentioning
confidence: 99%
“…Igarashi et al demonstrated a reduced level of glutamate as an indicator of synaptic dysfunction measured by using glutamate CEST in the parietal cortex, but not in the hippocampus of 5×FAD mice [135]. Chen et al demonstrated that creatine CEST detection of creatine level were reduced in the cortex and corpus callosum of APP/PS1 mice compared to wild-type mice at 6 months-of-age [136]. Chen et al showed that reduced saturation transfer difference for the composite protein amide proton in APP/PS1 mice at compared to the age-matched wild-type mice [137].…”
Section: Chemical Exchange Saturation Transfer (Cest)mentioning
confidence: 99%
“…The authors declare no completing interest relevant to the submitted manuscript. T2*w GE, T2w SE APP/PS1, APPV717I mice [32,49,225,226] CESL APP/PS1 mice [36] T1w, CE-MR APP/PS1, PDAPP mice [227] 3D GE T2*w APP/PS1, PS1 mice [228] MTC APP/PS1 mice T2*, Gd-DTPA-K6Aβ1-30 APP/PS1, APPswe mice [46] T1w, Cyanine-Gd(III) complex 5×FAD mice CEST APP23 mice [133] APP/PS1 mice [136,137].…”
Section: Declaration Of Interestmentioning
confidence: 99%